Vredenburg met koeienmarkt, tussen Korte Viestraat en Willemstraat. Achtergrond: St. Augustinuskerk - Marcussen, C. (1877)
Vredenburg met koeienmarkt, tussen Korte Viestraat en Willemstraat. Achtergrond: St. Augustinuskerk.